New Aspects Regarding the Role of Banks in Economy in the Context of Globalization - Riana Iren RADU; Angelica STRATULAT (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics, 2017)
Globalization is a concept of widespread international circulation, launched since the last decade of the previous century in all academic, financial and commercial environments. Globalization has been a subject of debate, both for and against, through its differentiation due to the economic progress of the various participants in the process. In this paper we aimed to address the evolution of the banking phenomenon in the context of globalization and to highlight the differences in the structure in banking according to the main global financial indicators.